2017
DOI: 10.31341/jios.41.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Bitcoin Cryptosystem with Other Common Internet Transaction Systems by AHP Technique

Abstract: This paper describes proposed methodology for evaluation of critical systems and prioritization of critical risks and assets identified in highly secured information systems. For different types of information assets or security environments it is necessary to apply different techniques and methods for their prioritization and evaluation. In this article, VECTOR matrix method for prioritization of critical assets and critical risks is explained and integrated into AHP (Analytic Hierarchy Process) technique as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Hacioglu et al [66] employed the combined approach of AHP and F-TOPSIS to create cryptocurrency mining strategies. Maček and Alagić [67] evaluated the performance of the bitcoin cryptosystem with AHP. Applying fuzzy CODAS, Katrancı and Kundakcı [68] assessed some cryptocurrencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hacioglu et al [66] employed the combined approach of AHP and F-TOPSIS to create cryptocurrency mining strategies. Maček and Alagić [67] evaluated the performance of the bitcoin cryptosystem with AHP. Applying fuzzy CODAS, Katrancı and Kundakcı [68] assessed some cryptocurrencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This MCDM approach considers a hierarchical structure of objectives, criteria, and alternatives to make complex decisions. Maček and Alagić [17] present an AHP-based approach to evaluate the security characteristics of the Bitcoin cryptocurrency system in comparison to other widely used online transaction systems.…”
Section: Related Workmentioning
confidence: 99%
“…Čičin-Šain (2017) found out that the "Croatian income/profit tax system is adequate to accommodate all the tax problems regarding the taxation of the transfer of BitCoin and therefore there is no need to adopt a new regulation". Maček et al (2017) researched the safety aspects of the Bitcoin IT network and concluded that in comparison with e-banking or m-banking as well as with all the aspects of e-commerce, Bitcoin is the least important for the stable IT business". Turudić et al (2017) considered the usage of the cryptocurrencies in international exchange business and concluded that "the Blockchain has limitless applications in the international exchange business and consequently there will be more and more companies that will internally use the Blockchain technology for the international exchange business".…”
Section: Literature Reviewmentioning
confidence: 99%